Spine injuries in gymnasts - Makovitch, S.; Eng, C. (Gymnastics medicine - evaluation, management and rehabilitation, 2020)
Reports of spine injuries in the gymnast are common. An epidemiological study of female collegiate gymnasts from the 1988-1989 through 2003-2004 seasons revealed that low back strains were the third most common practice and competition injury reported at 6% and 3% of all injuries, respectively. However, this injury surveillance data only captured acute injuries. Another 18-month prospective study of Australian elite and sub-elite female gymnasts found that lower back injuries were the second most common injury reported at 14.9% of all injuries. A more recent analysis of women's gymnastics data from the NCAA Injury Surveillance Program during the 2009-2010 through 2013-2014 academic years reported trunk injuries as the third most frequent injury at 13.4%. Trunk injuries included the chest, abdomen, upper back, and lower back. Data from a single institution over a 21-year period in precollegiate female gymnasts found an overall incidence of back injuries of 11.1%. A study of level 4-10 female gymnasts, which classified injuries into acute and overuse, found that 8.8% of acute injuries involved the mid and low back and 18% of overuse injuries involved the low back. Further large-scale studies are needed to specify back injury patterns related to gender, age, competitive level, type of injury, and location. Given the high prevalence of back-related pain and injuries in the active gymnast, there is concern for repercussions later in life. Conflicting data exists on this question, although it appears most studies suggest no difference in back pain compared with the general population. A study of 64 former elite female gymnasts who competed during the 1970s showed no increased prevalence of back pain compared to age-matched controls. However, the authors do point out that over time, the demands of gymnastics training have become more complex with increased stress to the spine. Another study looked at both former elite male and female athletes. including gymnasts, with a mean follow-up of 13 years. Despite significantly more radiographic abnormalities in the thoracic and lumbar spine, there was no increased report of back pain compared to controls. In fact, the frequency of back pain in male gymnasts decreased from 85% to 67%.